2019
DOI: 10.2478/rrlm-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

miR-190, CDK1, MCM10 and NDC80 predict the prognosis of the patients with lung cancer

Abstract: Lung cancer (LC), which includes small-cell lung carcinoma (SCLC) and non-small-cell lung carcinoma (NSCLC), is common and has a high fatality rate. This study aimed to reveal the prognostic mechanisms of LC. GSE30219 was extracted from the Gene Expression Omnibus (GEO) database, and included 293 LC samples and 14 normal lung samples. Differentially expressed genes (DEGs) were identified using the Limma package, and subjected to pathway enrichment analysis using DAVID. MicroRNAs (miRNAs) targeting the DEGs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…It has previously been reported that some of these also regulate the P53 signaling pathway (Mirgayazova et al, 2019). The hub genes have been also found to be associated with various cancers (Burum-Auensen et al, 2010;Wierstra, 2013;Luo et al, 2014;Singh et al, 2014;Schneider et al, 2017;Gao and Wang, 2019). In this study, we found the expression of the hub genes was up-regulated in cancer samples compared with normal tissues.…”
Section: Discussionsupporting
confidence: 63%
“…It has previously been reported that some of these also regulate the P53 signaling pathway (Mirgayazova et al, 2019). The hub genes have been also found to be associated with various cancers (Burum-Auensen et al, 2010;Wierstra, 2013;Luo et al, 2014;Singh et al, 2014;Schneider et al, 2017;Gao and Wang, 2019). In this study, we found the expression of the hub genes was up-regulated in cancer samples compared with normal tissues.…”
Section: Discussionsupporting
confidence: 63%
“…Exciting new technologies and thousands of listing examples of various miRNAs that have been identified as potential biomarkers, outbreak current scientific publications. In previous issues of the Romanian Journal of Laboratory Medicine some miRNA-30c and miRNA-190 were presented with prognostic abilities in patients with colon and lung cancer, but also a series of miRNAs that can serve as biomarkers for the evaluation of the critically ill polytrauma patient respectively (28)(29)(30). However, there is still a long way to go for the analytical and clinical validation of these classes of biomarkers.…”
Section: The Importance Of Liquid Biopsies For Precision Medicinementioning
confidence: 99%
“…There is no literature linking a role for JPH1 in OAC or acid-sensing. JPH1 was among the upregulated genes in an analysis of lung cancer [ 120 ]. Zou et al [ 121 ] noted that the long non-coding form of JPH1 RNA, Lnc-JPH1-7, was upregulated 35-fold in TCGA samples of head-and-neck, squamous-cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%